The role of service providers’ skills in improving the evaluation of the quality of sports services - A field study on clients of fitness clubs in Latakia Governorate- - خيربك, دانيال; كندة علي ديب,; سنان حلوم , (Latakia University Journal - Economic and Legal Sciences Series, 2024)
This study aimed to determine the level of quality of sports services in the club under study, and to determine the impact of the technical skills of service providers on improving the quality of sports service, and to determine the impact of their behavioral skills on improving the quality of sports service in the club. The researcher relied on the deductive approach as a general approach of thinking, and the descriptive analytical approach was used as a general approach in this study. Secondary data from periodicals and master’s theses were used to formulate the theoretical framework. Primary data from a questionnaire organized by the researcher, after reviewing previous studies that dealt with the variables studied, was analyzed using SPSS (20). The most important results of this study were: There is an impact of the skills of service providers (behavioral and technical skills) on improving the quality of sports services in the club under study. Among the most important recommendations presented by the researcher: giving priority to listening to the needs and interests of customers, and responding to their inquiries immediately. This can be achieved by allocating a designated time for customers to ask questions and provide clear and concise answers on them.